Improved nutrient management regime for production of early generation seed of sweetpotato in the screenhouse - Atugonza, K.; Omongo, C.; Musana, P.; Namanda, S. (2025)
This research brief summarizes a nutrient optimization experiment conducted at Uganda’s National Crops Resources Research Institute (NaCRRI) in 2023–2024 to enhance sweetpotato pre-basic seed production in screenhouse conditions. Four fertilizer treatments—forest compost, forest compost + decomposed poultry manure, forest compost + urea (46%), and forest compost + NPK (25:5:5)—were tested on varieties NAROSPOT 1, Tanzania, and NASPOT 10 O (Kabode). The combination of forest compost and decomposed poultry manure yielded the highest vine multiplication rate (VMR) (49% increase) and lowest unit production cost (UGX 13 per cutting), especially for the variety Tanzania. In contrast, compost + urea resulted in the highest costs (UGX 25 per cutting). The findings identify the compost + manure combination as the most agronomically efficient and cost-effective nutrient regime for sustainable pre-basic seed production.